O analista no campo analisante: dos impasses às transformações possíveis - Tamburrino, Gina (2013)
This thesis results from an effort to penetrate questions regarding impasse that is formed and transformed in the relationship between the analyst and the analysand. The clinical work is understood and organized taking into consideration an intersubjective vertex, thus the concept of analyzing field is forged to demonstrate the analyst s implication in the formation and transformation of the shared unconscious fantasy. The highlight of the research is the presentation of the hypothesis that, in certain moments, the analyst s mind presents a dysfunctional quality in order to receive, to sustain and to prepare the field for the production of the analyzing pair. In these moments, the shared unconscious fantasy transforms itself into shared resistance: bulwarks , chronic enactments and acute enactments; the important thing to be investigated is how this kind of configuration is formed and how it transforms itself, always considering the dialectic impasse ↔ possible transformations. Besides it interests us the fact that the dysfunction in the analyzing field isn t always generated by the difficulties of a disturbed patient, it can also be caused by a disturbed analyst that, in such cases, becomes the main responsible for the functional inversion of the field to the detriment of the analysand. The main focus of this study is, above all, how the analyst wanders in the analyzing field beyond the non-analyzed questions